“From place to place and sea to sea”: The Art of Relating in R. L. Stevenson’s The Wrecker - Julie GAY (E-REA)
This paper aims to explore the fertile polysemy of the term “relating”, which may refer to the idea of connecting or linking heterogeneous elements together, but also to the action of recounting a story. It is my contention that analysing the relationship between these two concurrent meanings may help shed new light on Robert Louis Stevenson’s fictional art, which could be defined as essentially geopoetic. Indeed, relating a “globe-trotting story” like The Wrecker (406) not only entails connecting various spaces as the narration follows the character’s chaotic trajectory across the globe, but also weaving together the various genres associated with these spaces. At a narratological level, it moreover involves building a network of relations between the two narrators’ tales, and thus leaving clues for the reader to put together in the manner of a puzzle or a game of “dominoes” (406). The characters’ archipelagic circulation around the globe is therefore echoed by the narrator’s generic and narrative wanderings but also by the reader’s, whose role in the “relation” of the tale is crucial as it requires him to connect all of these heterogeneous elements together, and map them out into a coherent picture.